The environmental friendly relations of goat milk product manufacturing - Szigeti, Orsolya; Szakály, Zoltán (Acta Agraria Kaposváriensis, 2002)
The strategy of the Hungarian agriculture and rural development predicts a promising future to the breeding and raising of small ruminants (sheep, goat). Though, in the first half of the 1990s, the population of both breeds decreased dominantly, now their number is increasing. Goats can make perfect use of both those pasture areas that are not valuable for other animals and those ones that are not used for crop production any more because of their inefficient productivity. With a small amount of investment, a significant profit can be gained with a high quality management. Thus it can be an excellent source of income ever for the less capital-intensive entrepreneurs. 90% of the domestic stock can be found in groups of less than 25 animals at small-scale and family enterprises that is its role in human employment is also dominant. Due to the small dimensions of enterprises, they could hens a dominant role in region maintenance, too. These characteristics are equal to the principles supported by the EU. Small ruminants produce organic products that are more and more demanded and will become parts of modern nutrition in the future. There is a good market for goat milk and for the products made from it, as there is an increasing demand for healthier eating habits. Two trends are developing nationally. One way of milk processing is the production of traditional goat diary products (cheese, curd). These goods are considered as own products of Hungary, and can operate as Hungaricums. The other trend is represented by more complicated products produced by a developed technology. Products made from goat milk are more useful for the filling of a market niche than for the satisfying of heavy demands. As a consequence, basically the production of quality products should be preferred to mass production.
Keywords: goat milk product; friendly relations; quality and ecological product; healthy eating